THE FUTURE OF CRYPTO-CURRENCY IN THE ABSENCE OF REGULATION, SOCIAL AND LEGAL IMPACT - Joy, Akhigbe Iyen (PEOPLE: International Journal of Social Sciences, 2018)
The Internet revolution is fast outpacing the law and creating a newer world with the momentum of gripping the unwary crowd into a boundless world of anarchism. Money is defined as a medium of exchange, store of value, and a unit of account (www.cliffnotes.com Date of use: 28/10/2017). Crypto-currency is a new wake in the digital reality that is performing the above functions of money. There are about 1,541 crypto-currencies traded in 8,894 markets by exchangers (www.coinmarketcap.com Date of use: 28/01/2018). Prominent among these crypto currencies, is the Bitcoin which as a single coin had a monetary value of $0.05 USD in July 2010 and in November 2017, was valued at $18,000 (www.useyourselfmedia.today Date of use: 28/10/2017). The drivers of crypto-currencies are basically the block-chain which is a technology, others are the exchanges, financial services provider, wallet services provider and miners. Under most jurisdictions, the exchanges and service providers are either not regulated or partially regulated. Regulations in the financial sector, are tools used in monitoring the movement of funds, fraud, financial crimes and money laundering, criminal activities, as well as the protection of consumers. In the absence of regulation, this paper seeks to examine the trend and legality of the crypto currency as a virtual currency and its current and future impact on the society. To achieve this, some monetary regulations will be evaluated and an attempt will be made to adapt these regulations to the crypto-currency framework. At the end of the paper, challenges will be identified with a view to recommending a regulated regime in the use of crypto-currencies for a safer society and consumer protection.